Corrigendum: Food Allergy and Helicobacter pylori Infection: A Systematic Review - Zheng, Feei Ma; Abdul Majid, Noorizan; Yoshio, Yamaoka; Yeong, Yeh Lee (Frontiers Media, 2016)
Introduction: Based on the hygiene hypothesis, a low prevalence of Helicobacter pylori (H. pylori) infection may explain the recent high prevalence of allergic diseases including food allergy. However, there are very few studies that investigate the relationship between H. pylori and food allergy.